Passive acoustic monitoring data recorded by recorder SV1097 at mooring F4-21 in Fram Strait from 2022 to 2023 - Karolin Thomisch; Stefanie Spiesecke; Marlene Meister; Olaf Boebel (PANGAEA, 2025)
Passive acoustic monitoring (PAM) data were collected by recorder SV1097 of type Sono.Vault (manufactured by develogic GmbH, Hamburg, Germany) at 79.0003° N, 7.0004° E, mooring F4-21, in Fram Strait. During a deployment period from July 2022 to July 2024, passive acoustic data were collected from July 2022 to August 2023 (recording period) by SV1097 as part of the Frontiers in Arctic Marine Monitoring (FRAM) observatory in Fram Strait. The recorder was moored at 300 m depth and scheduled to record continuously at a sample rate of 48,000 Hz. Further details about the data acquisition and processing of this data set can be found in the accompanying metadata file (see Additional metadata) as well as the data processing report (see Data Processing Report). Passive acoustic data archived here represent data processing Level 1+, according to the standards defined in the associated Standard Operation Procedure (SOP) Glossary (Thomisch et al. 2023a). Further information on data processing with regard to data preparation and standardization can be found in the associated SOP Part 1: Data preparation and standardization (Thomisch et al. 2023b).